Diskriminasi Terhadap Perempuan Pekerja Pemulung Sampah Dalam Analisis Gender - Zuhriana, Desi (Jurnal Riset Daerah, 2021)
This research is intended to determine the forms of discrimination against women and the supporting factors for discrimination against women. The researcher's background raises the title about discrimination against women because many people cannot distinguish between natural and construct, which results in discrimination against women. With the formulation of the problem of forms of discrimination that occur in women in Ngablak Sitimulyo Hamlet, Piyungan, Bantul. The supporting factor occurred discrimination against women in Ngablak Sitimulyo Hamlet, Piyungan, Bantul This research was conducted in Dusun Ngablak RT 03 and RT 05 and is a qualitative field research. The method used in collecting data was to use primary sources in the form of interviews with related subjects, namely women in RT 03 and RT 05 Dusun Ngablak with a total sample size of eight people. Sources of data used are secondary data sources in the form of articles and documents related to the research theme. Meanwhile, for data collection, the researcher used the method of observation, interview and documentation. Data analysis is in the form of an explanation of the situation in the research location which is then described descriptively and narrative. Data analysis was performed by describing the data as a whole and analyzed using the patriarchal theory.The results showed that in the forms of discrimination against women who were interviewed with women or wives in RT 03 and RT 05 In Ngablak hamlet, there were several forms of discrimination against all informants openly, namely stereotypes, for example one of the residents felt from her own husband, namely typing in the business. the household and even when the child does not want to do the recitation the wife is to blame, subordination, for example, some women in Ngablak Hamlet feel that they are placed in the second position in society because they think that men win with everything, double burden, for example some women feel double work other than in the domestic space women also work in public rung and violence against women is an example because the double burden felt by women in Dusun Ngablak RT 03 and RT 05 resulted in violence against women. There are also several supporting factors including internal factors which include biological factors, religious factors and awareness factors, then the second is external factors which include cultural factors and economic factors